The Financial Impact of Charter Schools on School Districts - Edward Muir; F. Howard Nelson; Rachel Drown (Educational Considerations, 2000)
Charter schools are new or converted schools “chartered” by agents of the state, which offer families options in addition to those choices available through their school district.